Both "canonical" and "immunological" preeclampsia subtypes demonstrate changes in placental immune cell composition. (August 2019) - Leavey, Katherine; Grynspan, David; Cox, Brian J.
Abstract: Our prior work investigating the heterogeneity of preeclampsia identified multiple placental subtypes of this disorder, including a "canonical" group with maternal vascular malperfusion and an "immunological" group with signs of allograft rejection. Here, we perform a pilot immunohistochemistry study to investigate if an increase in infiltrating maternal immune cells is contributing to the "immunological" pathology subtype. This revealed an enrichment of monocytes and/or neutrophils (CD68  +  and MPO +  cells) in the intervillous space of these placentas. Surprisingly, "canonical" samples also demonstrated a significant result, with decreased CD68 staining. As such, further immunohistochemistry to assess immune contributions in preeclampsia subtypes is warranted. Highlights: Immune cell-specific genes are upregulated in "immunological" PE placentas. Immunohistochemistry confirmed the increased presence of monocytes and neutrophils. Surprisingly, "canonical" PE placentas revealed decreased monocytes/macrophages.